The Development of Self-Care Therapy Application: A pilot test - Hamdan, Afrina Sakinah; Zulhairi, Nur Izzati Aqilah; Abd Malek, Sarah Izzaty; Mohamed, Juliana (Multidisciplinary Applied Research and Innovation, 2022)
Due to the increasing of COVID-19 cases, countless of people loss their source of income especially salaried workers. This happens unexpectedly because world’s economy is collapsing due to the Movement Control Order (MCO). Not only for the worker, but students are also affected because online learning method has been running for almost a year now and students may feel stressed out. Self-care therapy application has been developed to help people manage their mental health condition and train people to calm their depression and anxiety. The ADDIE model has been used to build this application. This application will give hope and strength for all people to keep on going and not giving up. In future, people will know how to reach out for help when they are feeling sad or stress with everything.